A importância da elaboração e avaliação de projetos: perspectiva hipotética acerca da viabilidade de uma empresa no município de Santarém/PA - PEREIRA, Mateus Gualberto (Universidade Federal do Oeste do Pará, 2024)
The intention to launch a new product or make a new investment is crucial to carry out an assessment of the economic and financial viability of the project. This involves analyzing whether the investment will bring a positive or negative return, as well as estimating the magnitude of that return. The objective of this study is to analyze a hypothetical project and demonstrate the relevance of theoretical and practical knowledge on the subject to enable, using indicators from investment analysis, the viability of a business. It addresses the local economy of Santarém, the investment sectors. The research includes a bibliographical review on the economic and financial feasibility analysis, as well as documental research for instruction in the steps of preparing an investment. It should be noted that an undertaking must boost the municipality, through tax collection and the creation of new jobs. Therefore, the main characteristics of the Santarém market, where the study is carried out, must be considered when preparing a business project, the demand for products or services, the supply of raw materials, the location and the possibility of contributing to the development local. As a result, in addition to providing subsidies for the preparation of economic projects, a feasibility analysis of the project in question is carried out. Based on the results of the indicators, it is concluded that the project in question is economically viable for the company or investor. When carrying out a feasibility analysis, it ends up being a differential for the contribution to the success of a company in a region in the process of economic expansion, such as the Amazon, where Santarém/PA is located..